Regression Analysis to Predict the Impact of High Neutral Detergent Fiber Ingredients on Carcass Yield - J. Soto; M. D. Tokach; S. S. Dritz; M. A. Goncalves; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
Research has shown that carcass yield is reduced when feeding distillers dried grains with solubles (DDGS) or other high fiber ingredients. Considering the financial implications of changing carcass yield, the objective of this project was to develop regression equations to accurately estimate carcass yield from dietary NDF withdrawal strategies. Data from 8 trials originating from 5 journal articles, 2 theses, and 1 technical memo were used to develop a regression equation to predict carcass yield. The regression analysis showed that number of days in the withdrawal period (WP), NDF level in the dietary phase prior to the final phase (NDF1), NDF level in the last dietary phase before marketing (NDF2), and the interaction between NDF2 and WP (NDF2 × WP), were the most important variables in the dataset to predict carcass yield. The resulting regression equation: carcass yield, % = 0.03492 × WP (d) – 0.05092 × NDF1 (%) – 0.06897 × NDF2 (%) – 0.00289 (NDF2 (%) × WP (d)) + 76.0769 may be used to predict the influence of dietary NDF and NDF withdrawal strategy on carcass yield.
Keywords: neutral detergent fiber; carcass yield; mixed models; regression equations